Implementation of the Quality Management Concept in Improving Services at the Investment and One-Stop Integrated Services Service of North Penajam Paser Regency - Ariwibowo, Nuri; Sadly Abdul Djabar, Hasniaty, (Pascasarjana STIE Amkop Makassar, 2024)
Study This aim For analyze How implementation quality management to improve services at the North Penajam Paser Regency Investment and One-Stop Integrated Services Service . Focus main from study This is For evaluate extent of management quality implemented in context service public and how its implementation can impact on improvement quality service .Research methods used is approach qualitative with interview deep to a number informant key , incl head of DPMPTSP, Secretary , Head Field Planning , Climate Development , Promotion and Control Implementation Capital Investment , Head Field Maintenance Service Licensing and Non- Licensing , Head Field Complaints , Policies , Data and Reporting Service as well as Head of General Subdivision . Data is collected through interviews and studies documentation For get deep understanding about processes , procedures and obstacles faced in implementation management quality . Data analysis was carried out with use technique analysis interactive model for evaluate How elements management quality can integrated in a way effective in structure and culture organization .Research result show that implementation management quality own impact real For increase quality services at the District DPMPTSP Penajam Paser Utara, however there is a number of necessary challenge resolved . Findings show necessity commitment strong managerial skills , training and involvement employees , as well continuous process improvement For reach optimal results . Study This recommend approach structured For overcome obstacles it and improve efficiency as well as satisfaction service public in the DPMPTSP environment .Keywords : Management Quality ; Service ; Capital Investment Service ; PTSP; Regency North Sharpener Paser